Knowledge and perceptions regarding Coronavirus (COVID-19) among pediatric dentists during lockdown period - Mallineni, Sreekanth Kumar; Nuvvula, Sivakumar; Bhumireddy, Jaya Chandra; Ismail, Ahmad Faisal; Verma, Priya; Sajja, Rishitha; Alassaf, Abdullah; Almulhim, Basim; Alghamdi, Sara; Saha, Anupam; Goyal, Virinder; Namineni, Srinivas (MDPI, 2022)
Aim: To assess the knowledge and perceptions of COVID-19 among pediatric dentists based on their dependent source of information. Methods: A descriptive-analytical cross-sectional survey using a self-administered questionnaire with 23 questions was sent via Google forms to pediatric dentists. All participants were divided into three groups [postgraduate residents (PGs), private practitioners (PP), and faculty (F)]. The comparison of knowledge and perception scores was made based on occupation, source of information, and descriptive statistics used for the analysis using SPSS 21.0 (IBM, Armonk, NY, USA). Results: A total of 291 pediatric dentists completed the survey, and the majority of them were females (65%). Overall, good mean scores were obtained for knowledge (9.2 ± 1.07) and perceptions (5.6 ± 1.5). The majority of the participants used health authorities (45%) to obtain updates on COVID-19, while social media (35.1%) and both (19.6%) accounted for the next two. A statistically significant difference (p < 0.05) was found among different pediatric dentists groups for relying on the source of information. Conclusion: Overall good pediatric dentists showed sufficient knowledge regarding COVID-19. The pediatric dentists’ age, occupation, and source of information influenced knowledge regarding COVID-19, whereas perceptions were influenced by age and gender of the participants. Health authorities successfully educated pediatric dentists than the social media